BORROWINGS FROM ENGLISH IN A PHILIPPINE REGIONAL LANGUAGE: IMPLICATIONS FOR LANGUAGE TEACHING - Fina felisa lavalle alcudia; Ma. AsMa. Asuncion uncion Christine V. Dequilla; Daisy A rosano (STBA LIA - Jakarta, 2019)
This sociolinguistic study was conducted in conjunction with a project on the development of a course syllabus and instructional materials for the teaching of Hiligaynon as mother tongue in Region VI Western Visayas, Philippines. A corpora of the first one thousand commonly used in Hiligaynon was developed through an adopted concordancing software. Derived from corpus linguistics, a corpora study is a descriptive method of studying language in context and is ideal for a functional-based analysis of language (Meyer, 2004). The words were culled from various genres in the local language. These were analyzed for meaning, part of speech, and level of usage in Hiligaynon discourse. The corpora, however, yielded codes borrowed from English. A semantic, syntactic, and functional analysis of the words led to the following categories: adapted words, convenient alternative words, words occurring in compound nouns, indigenized spelling, indigenized pronunciation, and clipped words. The results imply that a purist approach in teaching mother tongue will limit the learners’ acquisition of vocabulary words and skills in meaning-making. It is recommended that language teachers take an eclectic posturing that considers multi-modalities, translanguaging, authenticity, linguistic resourcing, and entextualization.